Effectiveness of Treatments for Ocular Toxoplasmosis. (17th February 2020) - Casoy, Julio; Nascimento, Heloisa; Silva, Luci Meire P.; Fernández-Zamora, Yuslay; Muccioli, Cristina; Dias, João Rafael de Oliveira; Nóbrega, Mário Junqueira; Nóbrega, Heloísa Amaral Junqueira; Zummo, Jacqueline; Belfort, Rubens
ABSTRACT: Purpose : To evaluate the effectiveness of treatments for ocular toxoplasmosis (OT). Methods : A review of charts was conducted from patients who experienced an active episode of OT treated at the Federal University of São Paulo and associated sites. OT charts were reviewed to determine treatment effectiveness based on clinical judgment, taking clinical course and outcome into consideration in addition to change in best-corrected visual acuity. Treatment emergent adverse events (TEAEs) were used to assess safety. Results : Overall, 451/1200 patient charts met the inclusion criteria. The most commonly prescribed treatment was trimethoprim + sulfamethoxazole (52.3%) followed by pyrimethamine + sulfadiazine (28%). Treatment was successful in 96.9% of patients. Irrespective of the treatment, active lesions were resolved in 63.9% of patients within 6 weeks. Vision improved in 56.3% of patients. The incidence of TEAEs was low (10%). Conclusions : All treatments were effective for active episodes of OT, with few side effects.